Lindsay tumour - C., Vignesh N.; D., Vinodh; S., Maniselvi; R., Kannan (International Surgery Journal, 2021)
The follicular tumours with nuclear features of papillary carcinoma are categorised as follicular variant of papillary thyroid carcinoma (FVPTC). They exhibit biologic and molecular properties that are different from conventional papillary thyroid cancer. Solid encapsulated follicular variant of papillary carcinoma of thyroid is termed as Lindsay tumour. Since they are encapsulated, they follow an indolent course. We present a case of Lindsay tumour in a 34-year-old female, who presented with swelling in the neck for six months. She had no other specific complaints. On local examination of her neck, there was a hemispherical swelling of size 6×5×2 cm, found in the midline which moves with deglutition. The swelling was firm in consistency and its surface was nodular. There were no palpable lymph nodes in the neck. The ultrasonogram of her neck revealed multinodular goitre. The fine needle aspiration cytology from neck swelling revealed colloid goitre with cystic degeneration. Her thyroid function tests were within normal limit. She was then, proceeded with total thyroidectomy. Her postoperative recovery was uneventful. Her histopathological report revealed an encapsulated follicular variant of papillary carcinoma of thyroid. She was then kept on half yearly follow-up with serum thyroglobulin. Therefore, this case provides an opportunity to review the encapsulated follicular variant of papillary carcinoma thyroid (Lindsay tumour) and its management.